Dipetalonema graciliformis (Freitas, 1964) from the red-handed tamarins (Saguinus midas, Linnaeus, 1758) in French Guiana - Laidoudi, Younes; Paolo Lia, Riccardo; Mendoza-Roldan, Jairo Alfonso; Modrý, David; de Broucker, Charles-Arnaud; Mediannikov, Oleg; Davoust, Bernard; Otranto, Domenico (Parasitology, 2021)
Six Dipetalonema species have been reported from Neotropical monkeys, Dipetalonema gracile, Dipetalonema graciliformis and Dipetalonema caudispina being the dominant species found in French Guiana primates. Adult filarioids isolated from the abdominal cavity of tamarins (Saguinus midas) in French Guiana were morphologically and molecularly identified as D. graciliformis. Phylogenetic analysis based on DNA and amino acid sequences of the cox1 gene as well as the concatenated sequences of the cox1 and the 18S genes indicated that D. graciliformis belongs to the clade 4 (ONC4) of Onchocercidae. Blast analysis of the 18S rDNA revealed that D. graciliformis in the studied tamarins is conspecific with the filarioid circulating in howler monkeys (Alouatta macconnelli) in French Guiana, previously referred to as unidentified Onchocercidae species.
Keywords: Animals; Dipetalonema; Female; Dipetalonema Infections; Francouzská Guyana; ženské pohlaví; infekce hlísticemi rodu Dipetalonema; nemoci opic; molecular phylogeny; Neotropical primate; Saguinus; Male; French Guiana; integrative taxonomy; Dipetalonema graciliformis; zvířata; mužské pohlaví; Monkey Diseases; Saguinus midas